2010
DOI: 10.1128/jvi.00060-10
|View full text |Cite
|
Sign up to set email alerts
|

The De Novo Methyltransferases DNMT3a and DNMT3b Target the Murine Gammaherpesvirus Immediate-Early Gene 50 Promoter during Establishment of Latency

Abstract: The role of epigenetic modifications in the regulation of gammaherpesvirus latency has been a subject of active study for more than 20 years. DNA methylation, associated with transcriptional silencing in mammalian genomes, has been shown to be an important mechanism in the transcriptional control of several key gammaherpesvirus genes. In particular, DNA methylation of the functionally conserved immediate-early replication and transcription activator (RTA) has been shown to regulate Epstein-Barr virus and Kapos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…For example, Dnmt3a and Dnmt3b association with HDACs is considered to help maintain chromatin in a compact and silent state [62,63]. While deletion or inhibition of HDAC1 and HDAC2 blocked B-cell development at the pre-BII cell stage [64,65], deletion of Dnmt3a and Dnmt3b does not impair B-cell development ( [36] and this study), although Igκ recombination is impacted. Furthermore, Dnmt3a was recently shown to be required for differentiation of hematopoietic stem cells [66].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, Dnmt3a and Dnmt3b association with HDACs is considered to help maintain chromatin in a compact and silent state [62,63]. While deletion or inhibition of HDAC1 and HDAC2 blocked B-cell development at the pre-BII cell stage [64,65], deletion of Dnmt3a and Dnmt3b does not impair B-cell development ( [36] and this study), although Igκ recombination is impacted. Furthermore, Dnmt3a was recently shown to be required for differentiation of hematopoietic stem cells [66].…”
Section: Discussionmentioning
confidence: 58%
“…1). Gray et al had used CD19-cre mice to delete these two enzymes [36] and had come to a similar conclusion regarding the normal presence of different B-cell populations. However, mb1-cre mice are known to induce more efficient B-cell specific deletion of floxed genes than the CD19-cre line, and allow complete deletion of floxed alleles already in the pre-BI compartment in the BM The V(D)J rearrangement process starts with the rearrangement of the IgH locus in pro-B and pre-BI cells, followed by IgL rearrangement in small pre-BII cells [6].…”
Section: Discussionmentioning
confidence: 88%
“…LANA can stabilize the repression of KSHV lytic cycle gene expression and its interactions with DNA methylation machinery may partly account for this repressing activity. Consistent with this finding is the observation that DNMT3a and 3b mediate CpG methylation and transcription repression of MHV68 ORF50 promoter in latently infected B-lymphocytes in vivo [34]. A remarkable series of findings have revealed a complex and paradoxical role of DNA methylation in the regulation of EBV lytic reactivation (reviewed in more detail in this journal series) [35-40].…”
Section: Epigenetic Controls Of Viral Gene Expressionmentioning
confidence: 75%
“…It correlates with CpG methylation and histone deacetylation [47], [48]. Methylation of the ORF50 promoter has been reported for MuHV-4 [49]; another study found a more important role for histone deacetylation [45]. Methylation can be reversed with 5-azacytidine, and histone acetylation with sodium butyrate or Trichostatin A.…”
Section: Discussionmentioning
confidence: 91%